Tandem mass tag-based quantitative proteomics and targeted hormone analysis reveal the response to insect herbivory stress in Ginseng (Panax ginseng, L.). - Haitao Li; Lixin Zhang; Xiang Han; Qi Zhang; Guangna Liu; Guofeng Zhang; Yurong Zhu; Hongyang Liu; Haowei Deng; Shuangli Liu; Guangsheng Xi (PLoS ONE)
Ginsenosides are the most important secondary metabolites of ginseng. Ginseng has developed certain insect resistance properties during the course of evolutionary environmental adaptation. However, the mechanism underlying the insect resistance of ginseng is poorly understood. To elucidate the insect resistance mechanism of ginseng, we performed stress experiments on ginseng inoculated with black chafer larvae. The contents of ginsenosides in the ginseng roots, stems and leaves were determined at 0, 72, 120 and 168 h after the inoculation of insects. The tandem-mass-tag technology was used to determine the protein phosphorylation sites. Plant hormones were analyzed by multiple reaction monitoring targeted metabolomics. The results showed that ginsenosides present in the stems and leaves were more responsive to insect herbivory treatment than those present in the roots. Through proteomics, we found that the expression of most of the differentially expressed proteins, including GAPC1, GAPC2, and CSD1, was downregulated by insect herbivory treatment, HSP81-3 expression was up-regulated under insect herbivory stress. Regarding plant hormones, abscisic acid (ABA), gibberellic acid, Typhasterol (TY), iopentene adenine (IP), Cytokinin Riboside (czR) and Thiamethasone (tZ) levels were increased by herbivory treatment. With the increase in herbivory treatment time, the levels of trans-Zeatin-riboside (tzR), Isopentenyl adenosine riboside (iPR), and indole-3-acetic acid (IAA) were increased after 168h. The levels of salicylic acid (SA), jasmonates (JA), cis-PODA, and JA-Ile were increased after 120h but decreased thereafter. Under stress conditions, the expression of many antioxidant-related proteins was down-regulated; however, HSP81-3 expression was up-regulated, indicating that the plants exhibited severe oxidative stress. In conclusion, HSP81-3 plays an important role in ABA-dependent regulations involved in response to insect herbivory stress in ginseng. GAPC1 and GAPC2 also participate in the process of anti-herbivory stress response in ginseng.